Creating (in) the Arctic: Investigating collaboration and location through a case study of the Arctic noir serial Thin Ice. (June 2023) - Grønlund, Anders
The Swedish/Icelandic coproduced serial Tunn is [ Thin Ice ] (2020) offers an insight into current possibilities and challenges of production in the Nordic Arctic region and the involvement of the developing Greenlandic screen industry. By analysing both off- and on-screen elements through a broad screen industry and location-driven approach, the explorative case study illustrates both a region and a screen industry in development as well as changing production practices. Furthermore, the article highlights the perceived value of location and cultural specificity in high-end TV drama from the multi-ethnic and multi-lingual Arctic region.